Intraoperative rupture of an interlobar bronchial artery aneurysm: a case report. Issue 1 (December 2015) - Tsunezuka, Yoshio; Tanaka, Nobuyoshi; Fujimori, Hideki
Abstract Here we report the rare case of an intraoperative bronchial artery aneurysm (BAA) rupture. An asymptomatic 52-year-old woman was found to have bilateral, multiple dilated bronchial arteries feeding the BAA that was further connected to the pulmonary artery on computed tomography and angiography. Transcatheter arterial embolization was thought not to be succeed. During a thoracoscopic procedure, the BAA ruptured suddenly and was treated with a thoracotomy under percutaneous cardiopulmonary support (PCPS). For anatomical complex BAA like the present case, the use of an open procedure and the preparation of PCPS are strongly recommended.